HUBUNGAN BEBAN KERJA MENTAL, MASA KERJA DAN USIA TERHADAP KEJADIAN STRES PADA PEKERJA PERUSAHAAN AKUAKULTUR DI BANYUWANGI: The Correlation Between Mental Workload, Work Period, and Age To The Occurrence Of Stress on Workers of Aquaculture Company in Banyuwangi - Yarshynta Aprilia Marshanty; Intan Ayu Kusuma Wardani; Jayanti Dian Eka Sari (Journal of Community Mental Health and Public Policy, 2019)
Stress is one of the body's response due to unbalanced demands and abilities. The workers group is one group that has the potential for stress. The impact of stress caused is very likely to affect work. The purpose of this study was to examine the relationship between mental workload and individual factors (work period, age) with stress at aquaculture company in Banyuwangi. This research was an observational study with cross sectional design. The sample of this research is 36 samples and it is a total population. The purpose of this study was to determine the correlation between variables, the research data were analyzed using the Spearman correlation test. The results showed that the majority of workers have a mental workload with a high category, stress conditions for workers are mostly in the low stress category In conclusion, there is no relationship between mental workload (p value = 0,123) and work period (p value = 0,096) with stress. However, there is a relationship between age and stress (p value = 0,023) and this relationship is negative (correlation coefficient = -0.281). Recommendations for companies are to pay attention to workload owned by workers, both mental and physical workloads, create health programs for workers, including physical and mental health, create a healthy and comfortable work environment, and create good relationships between workers and introduce stress management to workers, so the workers are able to prevent the adverse effects of stress that might be experienced.